On-farm study on intercropping of hybrid maize with short duration vegetables (Journal of the Bangladesh Agricultural University, 2014)
The experiment was conducted at Multi Location Testing (MLT) site, Netrakona during rabi season of 2009-10 and 2010-11 to study the feasibility of intercropping of hybrid maize with different short duration vegetables and economic returns. Three intercrop combinations of hybrid maize along with sole maize were arranged in Randomized Complete Block Design replicated six times. There were four treatments viz., T1- Sole crop of maize, T2 - Three rows of red amaranth (25 cm apart) in between two (75 cm apart) rows of Maize, T3 - Three rows of bush bean (25 cm apart) in between two (75 cm apart) rows of Maize and T4 -Three rows of garden pea (25 cm apart) in between two (75 cm apart) rows of Maize. Yield contributing characters and yield of maize did not varied significantly due to intercropping with vegetables. The grain yield of maize in intercropped combination varied from 7.30-7.43 t/ha. But the highest grain yield (7.68 t/ha) was in sole maize. Maize equivalent yields in the intercrops ranged from 10.67-14.96 t/ha. The highest maize equivalent yield (14.96 t/ha), gross return (Tk. 224400/ha), gross margin (Tk.166830/ha) and benefit cost ratio (3.90) were obtained in maize + garden pea combination. The lowest maize equivalent yield (7.68 t/ha), gross return (Tk. 115200/ha), gross margin (Tk. 64128/ha) and benefit cost ratio (2.26) were obtained from sole crop of maize. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18195 J. Bangladesh Agril. Univ. 11(1): 1-4, 2013